A Collection of Poems The Rivers, Seas, and Us by Morsidi M.H: The Story about Life (Malay Literature, 2022)
Poetry has become a popular choice among Bruneian writers. As a result, many of those who received the Southeast Asian Writers’ Awards came from the genre of poetry. Most recently, in 2021, Morsidi M.H was announced as the recipient of the award for his book, Kumpulan Sajak Sungai, Laut and Kita, which was published in 2021. This book contains 57 poems and is divided into four themes, namely Pulse and the Journey of Life (20 poems) , Homeland (7 poems), Nature and the Meaning of Life (12 poems), and Introspection and the Reality of Life (18 poems). In accordance with the contents and title, this collection of poetry presents life in line with time that is always moving forward. It works on the poet’s imagination, wisdom, and emotions to produce the poems. In the Pulse and Journey of Life section alone, there is a connection between one poem and another. This attracts attention to be used as research with the objective to study and interpret all the events that the poet went through during the passage of time recorded in the form of verses of his poems. A close reading of the poems in the Pulse and Journey of Life section is not enough. Therefore, it is coupled with an expressive approach to achieve the objective of this study more effectively. The findings of this research showed that these poems share the meaning of life, which is a journey that is not considered too easy to go through, especially when confronted with many faces of human nature. This journey of life is passed along with the passage of time, and it is finally realized that there is no best way to follow this journey of life except with faith and the guidance of Islamic teachings.